1955
DOI: 10.3733/hilg.v24n07p143
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing, keeping quality, and compositional changes during curing and storage of sweet potatoes

Abstract: California's mild climate has led to handling and storage practices with sweet potatoes that do not necessarily provide optimum conditions for wound healing. Experiments were conducted during a four-year period with three varieties on San Joaquin Valley farms to determine whether a curing period in a warm house, such as is customary in other areas, would favor wound healing and reduce storage losses and quality changes. A two-week curing period in a warm house, with a temperature of around 85°F and high relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The concepts regarding the chronology of wound responses in plants were developed initially with sweet potato (Artschwager and Starrett 1931), and later studies confirmed and elaborated upon earlier observations (Morris and Mann 1955, Strider and McCombs 1958, McClure 1960.…”
Section: Anatomy Of Wound Response In Barkmentioning
confidence: 64%
“…The concepts regarding the chronology of wound responses in plants were developed initially with sweet potato (Artschwager and Starrett 1931), and later studies confirmed and elaborated upon earlier observations (Morris and Mann 1955, Strider and McCombs 1958, McClure 1960.…”
Section: Anatomy Of Wound Response In Barkmentioning
confidence: 64%
“…There are numerous reports on sugar changes in sweetpotato during storage (Lewthwaite et al, 1997;Takahata et al, 1996;Ajlouni and Hamdy, 1988;Truong et al, 1986;Picha, 1986;Morris et al, 1955), because the composition and concentration of free sugars are important components of eating quality. Sugar-metabolizing enzymes such as invertases, sucrosesynthase (SS), and sucrose phosphate synthetase (SPS) likely influence sugar levels in sweetpotato roots during storage.…”
Section: Introductionmentioning
confidence: 97%
“…Wounding predisposes the roots to infection by pathogens (Lauritzen, 1935) and to desiccation during storage (Morris & Mann, 1955 ;Weimer & Harter, 1921) . Wounding predisposes the roots to infection by pathogens (Lauritzen, 1935) and to desiccation during storage (Morris & Mann, 1955 ;Weimer & Harter, 1921) .…”
Section: Introductionmentioning
confidence: 99%